Visual Analytics for Innovation and R&D Intelligence: The methodology presented offers practitioners a data-driven, visual analytic approach to understand and support their innovation and R&D intelligence activities. Issue 3 (4th May 2023) - Basole, Rahul C.
Abstract: Overview: Innovation is critical to the growth and survival of companies across industries and geographies. Over time, however, sources of innovation have become much more diverse, and a systematic understanding of the complex and dynamic innovation landscape is challenging. This paper describes the value and impact of using a data-driven, visual analytic approach for innovation and R&D intelligence. I outline a methodology with which to approach visual analytic innovation and R&D intelligence, present illustrative mini-case studies, and frame the findings into key considerations and elements of the intelligence decision space. The paper contributes to practical and theoretical understanding of how emerging computational and analytical approaches can support innovation and R&D activities. It concludes with practical implications and future research directions.